PELAKSANAAN KONTRAK KERJA PEMBANGUNAN RUMAH PADA PT. RIAU KARYA MANDIRI DI PEKANBARU - Theola Ramadhani; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
PT. Riau Karya Mandiri is a company engaged in property, especially housing, in the construction of houses the developer entered into an agreement with laborers, contractors, and foremen, where the employment clause is contained in a written agreement or employment contract. The purpose of this thesis is; First, to find out the implementation of a work contract between the developer of PT. Riau Karya Mandiri with the construction foreman carried out in the Prima Raya Lestari housing complex; Second, to find out what factors caused the default construction foreman in implementing the work contract for the construction of houses with the developer; Third, to find out the settlement of the defaults carried out by the foreman against the developer related to the implementation of the housing construction agreement in Prima Raya Lestari housing.This type of research is classified in the type of research Sociological law, namely research on the effectiveness of the law that is currently in effect, the nature of this research is descriptive, that is to describe systematically, the facts and characteristics of the object under study appropriately. The study was conducted in one of the housing estates of PT. Riau Karya Mandiri is Prima Raya Lestari housing, while the population and sample used are directors and developers of PT. Riau Karya Mandiri and the construction foreman related to the work contract for housing construction. Source of data used are primary data and secondary data, data collection techniques used are interviews.According to the results of the research problem there are 3 main things that can be concluded namely first, the implementation of the employment contract agreement at PT. Riau Karya Mandiri in Prima Raya Lestari housing which has not run according to the agreement clauses. Second, the main factors causing the default of the construction foreman in the implementation of the agreement are because of the absence of the foreman, replacement of the foreman and ineffectiveness of the work of the foreman and members in building houses. Third, the settlement of defaults carried out by the foreman against the developer that is resolved through mediation by the elect or trust of the parties with the results of mediation; The developer adds to the work of the foreman with new house construction work so that the wages of the foreman remain given and work on the previous house continues to run. Keywords: Employment Agreement, Developer, Construction Foreman